Influence Factors and Policy Analysis of Small and Microenterprises’ Sustainable Development: Empirical from Zhejiang - Pengyue Wu; Huijie Zhou (Discrete Dynamics in Nature and Society)
The sustainable development of enterprises is the driving force of national economic growth. The main objectives of this paper are to find what are all the influencing factors of enterprise sustainable development, how to produce the influence, and how to carry out effective strategy combination. This paper investigates 321 enterprises and analyzes their financial data from the aspects of market, internal management, industry, scale, products, and innovation ability. We find that fixed assets, information management level, and the overall quality of employees have the best driving force, reaching 0.132, 0.195, and 0.874, respectively. Enterprises also put more efforts on the improvement of internal management level and the expansion of industrial chain, which were 0.3778 and 0.2138, respectively. As far as the government's strategy of supporting and promoting tax policy is concerned, tax policy has a good independent impact, but when combined with other indicators, the impact effect is not significant. This shows that the promotion efficiency of the policy is low, and the applicability and pertinence need to be optimized. In addition, the promotion effect of innovation investment on sustainable development is poor, which shows that the innovation efficiency of small and microenterprises in Zhejiang Province is not high, and the ability to transform innovation resources into innovation output is insufficient.